Dehalogenases: from improved performance to potential microbial dehalogenation applications - Ang, Thiau Fu; Maiangwa, Jonathan Stallon; Salleh, Abu Bakar; Mohd Yahaya, Normi; Leow, Adam Thean Chor (M D P I AG, 2018)
The variety of halogenated substances and their derivatives widely used as pesticides, herbicides and other industrial products is of great concern due to the hazardous nature of these compounds owing to their toxicity, and persistent environmental pollution. Therefore, from the viewpoint of environmental technology, the need for environmentally relevant enzymes involved in biodegradation of these pollutants has received a great boost. One result of this great deal of attention has been the identification of environmentally relevant bacteria that produce hydrolytic dehalogenases—key enzymes which are considered cost-effective and eco-friendly in the removal and detoxification of these pollutants. These group of enzymes catalyzing the cleavage of the carbon-halogen bond of organohalogen compounds have potential applications in the chemical industry and bioremediation. The dehalogenases make use of fundamentally different strategies with a common mechanism to cleave carbon-halogen bonds whereby, an active-site carboxylate group attacks the substrate C atom bound to the halogen atom to form an ester intermediate and a halide ion with subsequent hydrolysis of the intermediate. Structurally, these dehalogenases have been characterized and shown to use substitution mechanisms that proceed via a covalent aspartyl intermediate. More so, the widest dehalogenation spectrum of electron acceptors tested with bacterial strains which could dehalogenate recalcitrant organohalides has further proven the versatility of bacterial dehalogenators to be considered when determining the fate of halogenated organics at contaminated sites. In this review, the general features of most widely studied bacterial dehalogenases, their structural properties, basis of the degradation of organohalides and their derivatives and how they have been improved for various applications is discussed.